Development of Rural Tourism: The Case of the Municipalities of Majur and the Citiy of Hrvatska Kostajnica - Rogina, Lorena; Tomašić, Lara; Hegeduš, Ivan (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
This paper analyses the potential and challenges of rural tourism development in the municipality of Majur and the town of Hrvatska Kostajnica, located in Sisak-Moslavina County. Rural tourism as a key factor for economic and social development holds significant potential for the revitalisation of these municipalities, the preservation of cultural and natural heritage and the strengthening of the local economy. The focus is on two examples of good practise – the Woonko Wool Centre and the Lenac OPG – which demonstrate how innovative approaches can improve the sustainability and competitiveness of the tourism offer. The analysis highlights the main barriers to development, such as inadequate infrastructure, limited promotion, complex administration and poor utilisation of EU funds. It also identifies key success factors, including a multidisciplinary approach, ongoing co-operation with stakeholders and adaptability of the strategy to changing conditions. Proposed actions include improving digital presence, strengthening local cooperation, developing thematic workshops, and funding infrastructure projects through the Rural Development Programme and other EU tenders. In conclusion, with the implementation of the proposed strategies and measures, rural tourism in Majur and Hrvatska Kostajnica can become a recognisable example of sustainable development that combines the preservation of cultural heritage and economic progress.